Recent Applications of Amphiphilic Copolymers in Drug Release Systems for Skin Treatment - Yudy Vanessa Cardona; Lizeth Geraldine Muñoz; Daniela Gutierrez Cardozo; Andrés Felipe Chamorro (MDPI AG, 2024)
Amphiphilic copolymers (ACs) are versatile systems with self-assembling and aggregating properties, enabling the formation of nanomaterials (NMs) such as micelles, vesicles, nanocapsules, and nanogels. These materials have been extensively explored for the delivery of various drugs and active compounds, enhancing the solubility and permeation of poorly water-soluble drugs into skin tissue. This improvement facilitates the treatment of skin diseases, including chronic conditions like cancer, as well as infections caused by bacteria, fungi, and viruses. This review summarizes recent applications of ACs in skin treatment, with a particular focus on their use in anti-cancer drug therapy. It covers the synthesis, classification, and characterization of ACs using various experimental techniques. Additionally, it discusses recent research on different drug delivery pathways using ACs, including encapsulation efficiency, release behavior, characteristics, applications, and responses to various chemical and physical stimuli (both in vivo and in vitro). Furthermore, this review provides a comprehensive analysis of the effects of ACs NMs on several skin diseases, highlighting their potential as alternative treatments.